Children of The Lamp : The Akhenaten Adventure - Kerr, P. B. (India Scholastic, 2008)
John and Philippa Gaunt are young djinns, and can grant wishes and make themselves disappear. They go to stay with their eccentric uncle Nimrod to perfect their fledgling magical abilities and end up on a desperate quest to locate the tomb of the pharaoh Akhenaten. Pitted against them is the most evil djinn in the universe.
Keywords: Twins -- Brothers and sisters -- Jinn